Working Capital Management and Profitability of Bottler’s Nepal Limited (Balaju) - Shrestha, Sanjay (Academic Voices: A Multidisciplinary Journal, 2019)
Working capital management is one of the essential determinants of firms’ market value because it directly affects the profitability. This study investigates the relationship between the working capital management and profitability and its impact on profitability in Bottler’s Nepal Limited (Balaju). Data analysis has been done using descriptive statistics, Pearson correlation, regression analysis, and F-test. The data used to analyze one (1) samples size, out of three which has found to be covering period 2009-2018 of listed multinational manufacturing company in Nepal. The working capital represents the variables of the Cash conversion period (CCP), Inventor Conversion Period (ICP), Receivable conversion Period (RCP), Payable deferred period (PDP), Current Ratio (CR) and the profitability including Return on Assets (ROA). The results are the finding of the impact of all five independent variables is tested together on dependent variable (ROA). From the model summary the value of R-square=0.851. It indicates that the five independent variables can explain approximately 85.10% of the proportion of variance of dependent variable. However, it is still left 14.9 % unexplained by these independent variables in this study. The results revealed that there is significant relationship between profitability and RCP, ICP and CCP and there is no significant relationship between profitability and PDP and CR.